Assessing the near infrared spectroscopy tool to explore phytochemical profile of Nothofagus antarctica (ñire) leaves - Mattera, Maria Gabriela; Batistelli, Marianela; Peri, Pablo Luis; Martinez Meier, Alejandro (Red Argentina de Ciencia y Tecnología Forestal, 2023)
Plants have evolved to detect adverse environmental conditions and generate diverse biochemical, morphological and physiological responses in order to grow and survive at a specific environment (Ahanger et al. 2017; Hossain et al. 2018). Plant tolerance to severe abiotic stresses (e.g., heat and drought) involves different strategies ranging from avoidance mechanisms to active protecting actions against damage (Estravis-Barcala et al. 2020). Signaling pathways that involve the reactive oxygen molecules (ROS) production and the activation of antioxidant response are recognized as protective mechanisms.